“Epistemology of the Closet”: Narrative Seduction and the Power in the Belly in Kaizer Nyatsumba’s “In Happiness and in Sorrow” - Mkhize, Jabulani (Journal of Literary Studies, 2017)
In this article, the author explores how Kaizer Nyatsumba’s short story, “In Happiness and in Sorrow”, deals with what Sedwick (2013) calls “the epistemology of the closet” by using interpellative strategies to dramatise narration as a seductive act (Chambers 1984). Starting from the premise that the power in the belly in Nyatsumba’s story lies precisely in the fact that the narrative is told from the perspective of the abandoned wife, the author employs Ross Chambers’ “renewed narratology” of studying “narrative situations in stories” to determine how Nyatsumba’s narrative makes its “point” by using seductive narrative manoeuvres to win the ideological assent of its readers. For this reason, the bulk of the argument in this article has, as its central thrust, a discussion of the modalities of narrative seduction in Nyatsumba’s narrative that can hold any reader’s attention spellbound, regardless of how a reader responds to the issues it raises. Opsomming In hierdie artikel ondersoek die outeur hoe Kaizer Nyatsumba se kortverhaal, “In Happiness and in Sorrow”, omgaan met dit wat Sedwick (2013) “die epistemologie van die binnekamer” noem, deur interpellatiewe strategieë aan te wend om verhaalkuns as ŉ verleidelike kuns te dramatiseer. Die outeur gaan van die veronderstelling uit dat die mag in die buik, in Nyatsumba se verhaal, juis opgesluit lê in die feit dat die verhaal vertel word vanuit die perspektief van die vrou wat verlaat is. Ross Chambers se “hernude narratologie” van die bestudering van “narratiewe situasies in stories” word aangewend om te bepaal hoe Nyatsumba se verhaal sy “punt” maak, deur verleidelike narratiewe tegnieke te gebruik om die ideologiese aanvaarding van sy lesers te wen. Om hierdie rede is die kern van die argument in hierdie artikel grootliks ŉ bespreking van die modaliteite van narratiewe verleiding in Nyatsumba se vertelling wat enige leser se aandag kan vasvang, ongeag hoe ŉ leser reageer op die kwessies wat dit aanroer.